Youth Subcultures ad Social Pedagogy - Smolík, Josef (Wydawnictwo Naukowe Uniwersytetu im.Adama Mickiewicza w Poznaniu, 2013)
This text deals with youth subcultures from the point of view of social pedagogy. Text introduces the basic terms such as culture, the dominant culture, subculture and counterculture and alternative culture. Furthermore there is analyzed the concept of subculture youth as well as the concept of lifestyle. A di erence between modern and postmodern approach to subcultures is also mentioned. Furthermore there is described the relationship between youth subcultures and social pedagogy, which is one of the disciplines that are devoted to youth subcultures. The nal part of the text brie y discusses selected youth subcultures in the Czech Republic and the negative manifestation of these subcultures.
Subkultury młodziezowe i pedagogika społeczna
Keywords: youth subcultures; lifestyle; social pedagogy; social pathology; leisureyouth; personal goods